Schemann, Hans; Mellado Blanco, Carmen; Buján, Patricia; Iglesias, Nelly; Larreta P.; Mansilla Ana (2013): Idiomatik Deutsch-Spanish/Diccionario idiomático alemán-español.Hamburg: Helmut Buske Verlag GmBH. 1202 pp. - Jasmina Markič; Vida Jesenšek (Verba Hispanica)
Schemann, Hans; Mellado Blanco, Carmen; Buján, Patricia; Iglesias, Nelly; Larreta P.; Mansilla Ana (2013): Idiomatik Deutsch-Spanish/Diccionario idiomático alemán-español.Hamburg: Helmut Buske Verlag GmBH. 1202 pp.